PERANCANGAN SISTEM INFORMASI ADMINISTRASI UNTUK PEMBAYARAN SPP SECARA ONLINE BERBASIS WEB - Sidhik, Mohammad Subekhi; Sibarani, Hiram Sulistio (ISTEK WIDURI, 2021)
In the current era of technology, it is necessary to innovate technology in the world of education. This research was explicitly designed with a web-based design to help better manage tuition payment data. The information system will be equipped with financial management features controlled by an online tuition payment administration information system. Currently, MI Nurul Falah is still facing several problems in data collection, and administrative processes for tuition payments carried out manually take a lot of time. Then the amount of data causes quite a lot of difficulties in storage, and the data becomes prone to damage and data loss. This descriptive study uses a qualitative approach with system requirements analysis, design, implementation, and testing. The system designed the SPP payment administration information website give well because the system was running as expected and could present reports on student payment transaction data such as data management, announcement data, historical payment data, payment transaction data, transaction report data, notes printing data, and setting data. According to the white box test calculations, the SPP payment transaction report is effective and efficient because the test results prove that no errors were found.